Dinuclear Rhenium Complexes with a Bridging Helicene‐bis‐bipyridine Ligand: Synthesis, Structure, and Photophysical and Chiroptical Properties. Issue 11 (23rd September 2020) - Saleh, Nidal; Kundu, Debsouri; Vanthuyne, Nicolas; Olesiak‐Banska, Joanna; Pniakowska, Anna; Matczyszyn, Katarzyna; Chang, Victoria Y.; Muller, Gilles; Williams, J. A. Gareth; Srebro‐Hooper, Monika; Autschbach, Jochen; Crassous, Jeanne
Abstract: By attaching pyridine groups to a diaza[6]helicene, a helical, bis‐ditopic, bis‐ N   N ‐coordinating ligand can be accessed. Dinuclear rhenium complexes featuring this bridging ligand, of the form [{Re(CO)3 Cl}2 ( N   N − N   N )], have been prepared and resolved to give enantiopure complexes. These complexes are phosphorescent in solution at room temperature under one‐ and two‐photon excitation. Their experimental chiroptical properties (optical rotation, electronic circular dichroism and circularly polarized emission) have been measured. They show, for instance, emission dissymmetry factors of c.a. ±3x10 −3 . Quantum‐chemical calculations indicate the importance of stereochemistry on the optical activity, pointing towards further design improvements in such types of complexes. Abstract : Chiral bridge : Enantiopure Re(I) complexes have been prepared from enantiopure helical bis‐bidentate bis‐bipyridine ligands and their photophysical and chiroptical properties, including two‐photon emission, have been studied. Quantum‐chemical calculations indicate the importance of stereochemistry on the optical activity.